1990
DOI: 10.1017/s004740450001438x
|View full text |Cite
|
Sign up to set email alerts
|

Accounting practices in medical interviews

Abstract: As doctors and patients communicate during medical interactions they both offer accounts and respond to them. By treating these accounts as interactional strategies which link social structure to social interaction we display how the medical interview is characterized by a moment-to-moment battle that mirrors and largely sustains the institutional authority and status of doctors and the reality of genders. (Medicine, communication, accounting practices, interactional strategies, institutional authority, profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…In other words, although my collection includes both consultant‐initiated and client‐initiated sequences, the consultant's advice is routinely not accounted for when client initiation is involved. This seems to parallel Fisher and Groce's (1990) finding that doctors, in their responses to patient questions, never append any accounts.…”
Section: Giving Advice Without Accountsmentioning
confidence: 56%
“…In other words, although my collection includes both consultant‐initiated and client‐initiated sequences, the consultant's advice is routinely not accounted for when client initiation is involved. This seems to parallel Fisher and Groce's (1990) finding that doctors, in their responses to patient questions, never append any accounts.…”
Section: Giving Advice Without Accountsmentioning
confidence: 56%
“…Physicians tend to give female patients more time, more explanations, and more responses to questions at the level of speech of the patients. On the other hand, physicians seem to be more likely to reject medical explanations from female patients [5], and female patients were spoken to in a less interested fashion than male patients by physicians of both sexes [6]. More women than men reported that they felt that physicians talked down to them (25% vs. 12%) and told them their problems were only in their heads (17% vs. 7%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…See Epperson & Zemel, 2008;Forrester, Ramsden, & Reason, 1997;Solomon, 1997;Ulvik & Salvesen, 2007;Yakel, 1997), conversation analysts have considered how speakers' talk performs a number of actions of potential interest to LIS scholars. These include "troubles telling" (Jefferson & Lee, 1992), raising new topics (Button & Casey, 1984), informing (Heritage, 1984;Schiffrin 1999), news giving (Maynard, 2003), advice giving (Heritage & Sefi, 1992;Pilnick, 2001), agreeing or disagreeing with prior talk (Kuo, 1994), claiming and challenging authority (Garcia & Parmer, 1999), managing discrepant perspectives (Lehtinen & Kääriäinen, 2005), counselling Silverman, 1997;He, 1995), negotiating (Karhila, Kettunen, Poskiparta, & Liimatainen, 2003), disclosing and responding to fears (Beach, Easter, Good, & Pigeron, 2005), presenting and discussing problems (Gill & Maynard, 2006;Robinson, 2006;Shaw & Kitzinger, 2007), repairing miscommunications (Ridley, Radford, & Mahon, 2002), making indirect requests (Gill, Halkowski, & Roberts, 2001;Weijts, Widdershoven, Kok, & Tomlow, 1993), discussing difficult or sensitive issues (Epperson & Zemel, 2008;Kinnell, 2001;Parry, 2004;Pilnick & Coleman, 2006), accounting for behavior (Fisher & Groce, 1990), making assessments (McHoul & Rapley, 2002;Jones, 2001), instructing (Epperson & Zemel, 2008), expla...…”
Section: Problem Statementmentioning
confidence: 99%